NILGAI, BOSELAPHUS TRAGOCAMELUS - A MAMMALIAN CROP PEST AROUND JODHPUR - GOYAL, S.K..; RAJPUROHIT, L.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Nilgai, Boselaphus tragocamelus is the largest common antelope found in open scrub forest in and around wild life sanctuaries, where little vegetation exists. Crop - damage by nilgai has been widely reported from all corners of India. A large number of nilgai occurs in and around agricultural areas and villages around Jodhpur viz. Beri-ganga, Daijar, Mandal - Nath, Kundli - Mata Mandir, Barli - Mandawata, Bamnia, Soorpura, Punjla, Jaji - Kalla and Banar. The followings reasons may be given for increasing nilgai in this region (a) lack of natural predators (b) deforestation for extensive agricultural activity (c) Overgrazing in the range land by domestic cattles and (d) the protection of these animals from Hindu communities who consider as near relative of cow. Tree cover consists mainly of Acacia senegal, A. nilotica, Prosopis juliflora, P. cineraria, Euphorbia caducifolia and Caparis decidua. These plants are generally used by nilgai as a daytime shelter, make hiding cover but they do not provide sufficient food for as per their requirement, therefore it goes for crop-raiding in the late evening and at night, jumping across 6 - 7 feet high stone wall, barbed fencing and fences of dead or live thorny plant material and any other offencing/barrier made to protect the crop-fields from wild and domestic animals. Due to habit of both grazing as well as browsing they devore every kind of farm species (both rabi and kharif crops). It has been observed that eating less but destroying more by trampling and causing damage are therefore regarded as serious mammalian crop pest and farmers wants to get rid of this unconventional pest. The farmers chase them away by just following them by making loud sound by crackers or air gun fires, following through tractors, empty tin or dried pumpkin filled with small stones and connected with strings. During this study (conducted from April to September, 1997) the feeding, food preferences and the measures used by local farmers to check this crop raider have been studied. Technically, corrals (enclosures), trenching or power fencing are suggested to mitigate the crop damage. Secondly animals could be translocated to wildlife sanctuaries from the sites they seen overcrowded or severe crop raiding problems.